Calling the Social Sciences Names - Philippe Fontaine (Revue d’Histoire des Sciences Humaines)
Throughout the 1950s, the use of the behavioral sciences label went together with the affirmation of social science’s collective ambitions to use quantitative methods and to practice interdisciplinary cooperation, but it also helped differentiation between and among disciplines by expressing different forms of engagement with natural science methods. In the Division of the Social Sciences at the University of Chicago, there were different conceptions of the behavioral sciences and the term referred to a variety of social scientific orientations along a spectrum running from biological to social determinism. The biologically-centered definition favored at the Committee on the Behavioral Sciences clashed with the mainstream definition’s emphasis on the loose emulation of natural science methods within a resolutely sociological framework.